Analisis Semiotika Foto Cerita Jurnalistik Haze Word Press Photo Contest 2022 Karya Abriansyah Liberto - Krisna Aldrin Gunawan; Sumaina Duku; Kararek (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2023)
This thesis is entitled "Semiotics Analysis of Photojournalistic Stories Word Press Photo Contest 2022 by Abriansyah Liberto". The formulation of the problem discussed in this thesis concerns the meaning of denotation, connotation, and myth as seen from Roland Barthes' semiotic method in a photo by Abriansyah Liberto. This thesis uses a qualitative method. The data collection technique in this thesis uses direct observation conducted on the Word Press Photo website, by observing and compiling photos of the Word Press Photo Contest 2022, Southeast Asia and Oceania, Long-Term Projects by Abriansyah Liberto. The interview was conducted by asking questions directly to the relevant parties, namely Abriansyah Liberto as the photographer, as well as documentation to view important documents and data related to the author. The number of photos analyzed in this thesis amounted to five photos out of twenty seven photos, the photos were analyzed using Roland Barthes' semiotic theory which found the results in the form of denotative meanings that describe the circumstances, behaviors, actions and attitudes that occur in the photos. then there is no Trick Effect (Photo Manipulation) connotation step that adds or subtracts objects to the photo. So that it can be ascertained the authenticity and truth of what happened to the five photos by Abrianysah Liberto according to the rules of photojournalism. And for the meaning of myth describes reality, sadness, damage, suffering, and situations that really happen.